PENINGKATAN KREATIVITAS GURU SMP MELALUI PENGEMBANGAN PERANGKAT PEMBELAJARAN INOVATIF - Sri Suryanti; Irwani Zawawi; Sarwo Edy; Nur Khomariyah; Roikhatul Jannah (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Teacher creativity and teaching effectiveness are two inseparable variables that affect student learning outcomes, this is the focus of this service activity. This service activity is proposed with 3 (three) things behind it, namely 1) evaluation of the results of the 2019 service, that 100% of teachers have implemented online learning; 2) the results of the team's experience in managing online learning at the University of Muhammadiyah Gresik; 3) The need to increase teacher competence in terms of developing HOTS-oriented innovative teaching materials, as demanded by 21st-century teachers. Based on these problems, through this PKM program, a solution is offered with the Assistance program to develop innovative HOTS-oriented teaching materials, which the team already has experienced very well in this area. The program is carried out through the stages of strengthening creative teaching concepts, workshops on developing innovative teaching materials oriented to HOTS, FGD validation of development results, then implementation with assistance from a service team and continued implementation independently by the schools.The result of this activity are 1) increased teacher understanding of creative teaching concepts; 2) produced innovative teaching materials' HOTS oriented; 3) teachers can implement innovative teaching materials' HOTS oriented independently